Clinical Significance of Extraluminal Compressions according to the Site of the Duodenum - Chul Byung Chae; Gwang Ha Kim; Sang Kyu Park; Moon Won Lee; Bong Eun Lee (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Background/Aims Differentiating extraluminal compressions from true subepithelial tumors in the duodenum by endoscopy alone is difficult. Endoscopic ultrasonography (EUS) is one of the most useful diagnostic modalities for this purpose. Extraluminal compression in the duodenum is occasionally observed, but its clinical significance has not been reported. Therefore, the aim of this study was to evaluate the clinical significance of extraluminal compression in the duodenum according to lesion location.Materials and Methods We retrospectively evaluated 22 patients diagnosed as having extraluminal compression in the duodenum based on EUS findings between January 2006 and December 2017. Some patients underwent abdominal computed tomography for accurate diagnosis. Results The location of the extraluminal compression was the duodenal bulb in 10 cases, the superior duodenal angle in 10 cases, and the second portion of the duodenum in 2 cases. Of the 22 cases, 12 were caused by normal structures, including vessels, the right kidney, the gallbladder, and the pancreas, and 10 were caused by pathological lesions, including the hepatic cyst, remnant cystic duct and dilated common bile duct after cholecystectomy; gallstones, gallbladder polyps, remnant cystic duct cancer, and pseudomyxoma peritoneii. The anterior wall of the duodenum was the most frequent location of extraluminal compression. However, the lesions in the anterior wall of the duodenal bulb and superior duodenal angle showed a high frequency of pathologic lesions, including malignancy. Conclusions If the extraluminal compression is found in the anterior wall of the duodenum, EUS is needed because of the high frequency of pathological lesions.